How do you evaluate (-4)(-2)-6(2-5)=
( the end should answer 26)
2 answers:
your answer is wright the answer of
(-4)(-2)-6(2-5) is 26
Answer:
PEMDAS
Parentheses and/or exponents, then multiplication and/or division, then +/-
parentheses first: (-4)(-2) - 6(2 - 5) = (-4)(-2) - 6(-3)
multiplication: (-4)(-2) - 6(-3) = 8 - (-18)
addition (subtracting a negative = add): 8 + 18 = 26
You might be interested in
Its 4 and 6
4 X 6= 24
6-4= 2
Answer:
what
Step-by-step explanation:
Answer:
m=49/4
Step-by-step explanation:
2560/5 would be 512 as a fraction with the same denominatir
Answer:1:b i think
2: 125
Step-by-step explanation: